Methods for the Determination of Transition Metal Impurities in Cyclotron-Produced Radiometals - Viktória Forgács; Anikó Fekete; Barbara Gyuricza; Dániel Szücs; György Trencsényi; Dezső Szikra (MDPI AG, 2022)
Cyclotron-produced radiometals must be separated from the irradiated target and purified from other metal impurities, which could interfere with the radiolabeling process. We compared different chromatographic and colorimetric methods to determine the amount of transition metals in radioactive samples. Besides commercially available colorimetric tests, 4-(2-pyridylazo)resorcinol and xylenol orange were used as a non-selective metal reagents, forming water-soluble chelates with most of the transition metals immediately. We compared the applicability of pre- and post-column derivatization, as well as colorimetric determination without separation. The studied chromatographic and colorimetric analyses are not suitable to completely replace atomic spectroscopic techniques for the determination of metal contaminants in radioactive samples, but they may play an important role in the development of methods for the purification of radiometals and in their routine quality control.